Effects of sex but not race and geographic origin on vaccine-induced HIV-specific antibody responses - Mbuya, Wilbert; Horvath, Augusta; Held, Kathrin; Maganga, Lucas; Hoelscher, Michael; Bekker, Linda-Gail; Duerr, Ann; Moodie, Zoe; Churchyard, Gavin; Keefer, Michael C.; Viegas, Edna; Moog, Christiane; et al. (Frontiers in Immunology, 2025)
BackgroundSex, race and geographic location may affect vaccine-induced immune responses, yet few preventive HIV vaccine trials have systematically evaluated such effects. The main objective of this study was therefore to examine the role of these factors on vaccine-induced HIV-specific immune responses within the HVTN 204 trial. This randomized, double-blinded, placebo-controlled phase 2 trial enrolled 480 Black and Caucasian adults from Africa and the Americas, who received a trivalent DNA-HIV-1 vaccine prime followed by a rAd5 vector HIV-1 vaccine boost.MethodsAvailable serum samples from baseline and four weeks after the final vaccination boost from Black (n=85, 59% female) and Caucasian (n=49, 51% female) HVTN 204 vaccine recipients from South Africa and the United States of America were studied using an Enzyme-Linked Immunosorbent Assay to determine titers of Envelope-specific IgG1, IgG3 and IgA antibodies. Recognition of linear Envelope peptide-specific IgG responses was mapped in a randomly selected subgroup analysis using a custom-designed peptide microarray (n = 41, 49% female). Associations between vaccine-induced Envelope-specific antibody responses and sex assigned at birth (female or male), race and geographic location were then analyzed by the Mann-Whitney U test, Fisher’s exact test and multivariate logistic regression.ResultsFour weeks post-final vaccination boost, we observed that Envelope-specific antibody titers were significantly increased for IgG1 but reduced for IgA in females (female vs. male median titer: 900 vs. 300, p=0.030 and <100 vs. 100, p=0.007, respectively). Multivariate logistic regression confirmed that female sex increased the odds for higher Envelope-specific IgG1 and low IgA titers compared to males. In terms of antibody epitopes, the V2 region was more frequently recognized in females than males (p=0.008). Race and geographic location had no apparent influence on antibody isotype titers investigated.ConclusionFemale sex was associated with higher vaccine-induced IgG Envelope-specific binding antibody titers and recognition of V2 region of HIV Envelope in HVTN 204 volunteers. No such associations were detected for race or geographic location. Understanding biological factors driving these sex-based differences may improve the design of a new generation of HIV vaccine candidates.